2021
DOI: 10.1021/acsami.1c16735
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Modified Silk Patch as a Next-Generation Ultrasound Coupling Medium

Abstract: There is an increasing interest in developing next-generation wearable ultrasound patch systems because of their wide range of applications, such as home healthcare systems and continuous monitoring systems for physiological conditions. A wearable ultrasound patch system requires a stable interface to the skin, an ultrasound coupling medium, a flexible transducer array, and miniaturized operating circuitries. In this study, we proposed a patch composed of calcium (Ca)-modified silk, which serves as both a stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…A five-cycle sine wave with 200 mV peak-to-peak voltage was generated by a function generator (33220A, Keysight Technologies, Santa Rosa, CA, USA), amplified by a radio frequency amplifier (5312-004 REV. X1, OPHIR RF Inc., Los Angeles, CA, USA), and transmitted through the matching layer by a commercial ultrasound transducer (HAGISONIC, Daejeon, Republic of Korea) [ 16 ]. Then, the received signal from a 0.5 mm diameter needle-type hydrophone (NH5000, Precision Acoustics, Dorchester, UK) was amplified and displayed on a digital oscilloscope (DSOX2022A, Keysight Technologies, Santa Rosa, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A five-cycle sine wave with 200 mV peak-to-peak voltage was generated by a function generator (33220A, Keysight Technologies, Santa Rosa, CA, USA), amplified by a radio frequency amplifier (5312-004 REV. X1, OPHIR RF Inc., Los Angeles, CA, USA), and transmitted through the matching layer by a commercial ultrasound transducer (HAGISONIC, Daejeon, Republic of Korea) [ 16 ]. Then, the received signal from a 0.5 mm diameter needle-type hydrophone (NH5000, Precision Acoustics, Dorchester, UK) was amplified and displayed on a digital oscilloscope (DSOX2022A, Keysight Technologies, Santa Rosa, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The speed of sound (c) and acoustic impedance (Z) of the matching layers were calculated with the measured difference in time of flight between transmitted and received signals, the thickness of the matching layer, and reference according to the Formulas (3) and (4) [ 16 ]. where d is the thickness of the matching layer, c o is the speed of sound in oil, ∆t 1 is the time-of-flight difference between the transmitted and received signal when the matching layer is absent, ∆t 2 is the time-of-flight difference between the transmitted and received signal when the matching layer is present, and ρ is the measured density of the matching layer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The design consisted of PZT blocks, serving as the piezoelectric islands, connected with polyimide (PI) serpentine hinges, allowing for stretchability between the otherwise rigid blocks. Lee et al showed that a calcium-modified silk could be used as an interface layer between sensor and skin for ultrasound transducer arrays and that it has a similar acoustic impedance to human skin [64]. Hamelmann et al also introduced an ultrasound array based on PZTs (Figure 4a) [15].…”
Section: Ultrasonic Signalsmentioning
confidence: 99%
“…Hamelmann et al also introduced an ultrasound array based on PZTs (Figure 4a) [15]. Other materials for stretchable ultrasound substrates include polyethylene naphthalate (PEN), PDMS, acrylic, and PET [60,64,65].…”
Section: Ultrasonic Signalsmentioning
confidence: 99%